Strategies for parenting by mothers and fathers with a mental illness. Issue 2 (11th February 2016) - van der Ende, P. C.; van Busschbach, J. T.; Nicholson, J.; Korevaar, E. L.; van Weeghel, J.
Accessible summary: What is known on the subject?: The combination of coping with their mental health problems and caring for children makes parents vulnerable. Family‐centred practice can help to maintain and strengthen important family relationships, and to identify and enhance the strengths of a parent with a mental illness, all contributing to the recovery of the person with the mental illness. What this paper adds to the existing knowledge?: Taking the strength and the opportunities formulated by parents themselves as a starting point is fairly new. Parents with severe mental illness find strength for parenting in several ways. They feel responsible, and this helps them to stay alert while parenting, whereas parenthood also offers a basis for social participation through school contacts and the child's friendships. Dedication to the parent role provides a focus; parents develop strengths and skills as they find a balance between attending to their own lives and caring for their children; and parenting prompts them to find adequate sources of social support. In this study these strategies were found to be the fundamentals of recovery related to parenting. What are the implications for practice?: Nurses can support and coach patients who are identified as parents, and self‐chosen parenting related goals are set and addressed. A family‐focused approach by nurses can be used to prevent problems for children and their families, identify their strengths as well as vulnerabilities, and address the challenges to build resilience. Abstract: Introduction: Understanding of the problems of parents with mental illness is growing. Gaining insight into strategies for parenting, while taking the opportunities formulated by these parents themselves as a starting point is fairly new. Question: What are the strategies of parents with a mental illness to be successful? Method: Experiences of 19 mothers and eight fathers with a mental illness were explored with in‐depth interviews. Data were content analysed, using qualitative methods. Results: Next to feelings of inadequacy, interviewees also describe how children enrich and structure their lives and are not only a burden but serve as distraction from problems. Developing activities that interest both child and parent provides avenues for emerging strength. Mental illness constrains fathers, but also gives opportunities to develop a meaningful relation with their children. Discussion: Strategies like being fully dedicated to the parental role, finding a balance between attention for one's own life and parenting and finding adequate sources of support are found to be fundamental for recovery in the parent role. Implications for practice: Peer groups can be of valuable help and mental health workers can support parents to set self‐chosen parenting related goals.